Rancang Bangun Sistem Informasi Pengelolaan Kaizen pada Divisi Hr Pt. Xyz Bekasi - Dyan Yuliana; Deva Satria (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
This research is entitled "Design and Build a Kaizen Information Management System in the HR Division of PT. XYZ Bekasi". The purpose of this research is to find out how the Kaizen Information Management System in the HR Division and the obstacles faced, as well as provide solutions to problems or obstacles in the system. From the results of the observations made, it can be concluded that the management of Kaizen data at PT. XYZ still uses the manual system. Of course, this causes several problems such as: Staff or Operators need a lot of time to approve the Kaizen form, difficulty reading the writing written on the form, and the form storage method is not neat and structured so that it is difficult in terms of management and reporting of the ongoing Kaizen program. The research methods used are Library Research and Field Research. There are three Actors/Users in this system, namely Staff/Operator, Manager and HR. Staff/Operator can only access the form management page, Managers can access to approve the form page, while HR can access all form management pages, make approvals, manage the theme of managing departments, manage accounts, manage reports and manage consultation schedules. The programming language used to create the Kaizen management system is PHP version 7 with the CodeIgniter framework with MySQL version 8. With the existence of the Kaizen Management Information System in the HR Division, it is hoped that it can simplify and accelerate the Kaizen management process.